A multiplex PCR for detection of knockdown resistance mutations, V1016G and F1534C, in pyrethroid-resistant Aedes aegypti - Jassada Saingamsook (2018)
© 2017 The Author(s). Background: Mutation of the voltage-gated sodium channel (VGSC) gene, or knockdown resistance (kdr) gene, is an important resistance mechanism of the dengue vector Aedes aegypti mosquitoes against pyrethroids. In many countries in Asia, a valine to glycine substitution (V1016G) and a phenylalanine to cysteine substitution (F1534C) are common in Ae. aegypti populations. The G1016 and C1534 allele frequencies have been increasing in recent years, and hence there is a need to have a simple and inexpensive tool to monitor the alleles in large scale. Methods: A multiplex PCR to detect V1016G and F1534C mutations has been developed in the current study. This study utilized primers from previous studies for detecting the mutation at position 1016 and newly designed primers to detect variants at position 1534. The PCR conditions were validated and compared with DNA sequencing using known kdr mutant laboratory strains and field collected mosquitoes. The efficacy of this method was also compared with allele-specific PCR (AS-PCR). Results: The results of our multiplex PCR were in complete agreement with sequencing data and better than the AS-PCR. In addition, the efficiency of two non-toxic DNA staining dyes, Ultrapower™ and RedSafe™, were evaluated by comparing with ethidium bromide (EtBr) and the results were satisfactory. Conclusions: Our multiplex PCR method is highly reliable and useful for implementing vector surveillance in locations where the two alleles co-occur.